Pathologic and molecular insights in nodal T-follicular helper cell lymphomas - Marques-Piubelli, Mario L.; Amador, Catalina; Vega, Francisco (Frontiers in Oncology, 2023)
T-follicular helper (TFH) cells are one of the T-cell subsets with a critical role in the regulation of germinal center (GC) reactions. TFH cells contribute to the positive selection of GC B-cells and promote plasma cell differentiation and antibody production. TFH cells express a unique phenotype characterized by PD-1hi, ICOShi, CD40Lhi, CD95hi, CTLAhi, CCR7lo, and CXCR5hi. Three main subtypes of nodal TFH lymphomas have been described: 1) angioimmunoblastic-type, 2) follicular-type, and 3) not otherwise specified (NOS). The diagnosis of these neoplasms can be challenging, and it is rendered based on a combination of clinical, laboratory, histopathologic, immunophenotypic, and molecular findings. The markers most frequently used to identify a TFH immunophenotype in paraffin-embedded tissue sections include PD1, CXCL13, CXCR5, ICOS, BCL6, and CD10. These neoplasms feature a characteristic and similar, but not identical, mutational landscape with mutations in epigenetic modifiers (TET2, DNMT3A, IDH2), RHOA, and T-cell receptor signaling genes. Here, we briefly review the biology of TFH cells and present a summary of the current pathologic, molecular, and genetic features of nodal lymphomas. We want to highlight the importance of performing a consistent panel of TFH immunostains and mutational studies in TCLs to identify TFH lymphomas.